Plant growth regulators priming enhances seed quality and enzymes activity in mungbean (Vigna radiata L.) - Tiwari, T.N.; Kamal, Dipti; Singh, R.K.; Prasad, S. Rajendra (Annals of Agricultural Research, 2016)
Field experiments were conducted at the research farm of Directorate of Seed Research, Mau to improve the germination, stand establishment, and growth of mungbean employing the seed priming techniques. Seeds of two mungbean varieties viz: Samrat and Pusa Vishal were sand primed with 50 ppm and 100 ppm solution of growth regulators viz. Gibberellic Acid (GA3), Indol Acetic Acid (IAA), Indol butyric acid (IBA) and Kinetin separately for 8 hours. Experiments were conducted in laboratory as well as in the cemented pots of 15 kg capacity. The results revealed that PGR priming showed significant enhancement in the seed quality parameters, growth, nitrate assimilatory enzymes and alpha amylase activity over unprimed control. Among treatments performance of GA3 @ 100 ppm was superior over others in respect of seed germination, field emergence, seedling growth, vigour index 1 & 2, nitrate assimilatory enzymes including nitrate reductase and nitrite reductase and germination enzyme alpha amylase.